Plano de gestão de dados para a produção de dados FAIR: O caso de uso FRAILSURVEY - André Filipe da Costa Maciel (2020)
The generalization of curation and the sharing of research data is a very current topic. In this context, the Data Management Plan emerges as an essential document, by promoting the production and sharing of data according to the FAIR principles. Researchers play a crucial role in this matter, and it's essential that they are made aware of the importance of Data Management Plans and data management practices. The development of a data management plan for the production of FAIR data, and the awareness of this project's researchers with concepts, resources and tools of Research Data Management are the main objectives of this work. In order to achieve them, the project and the research domain was studied and a document with recommendations related to the data management to the project was elaborated. These recommendations are the basis for carrying out the tasks associated with the two objectives. To evaluate the document produced and fulfill the objectives of the dissertation, a online questionnaire and a document with some questions was developed to obtain feedback from researchers. The results obtained are a Data Management Plan in accordance with the FAIR principles for FrailSurvey project and raising researcher's awareness to the importance of Research Data Management, increasing their knowledge about the concepts, resources, tools and practices. The followed methodology contributes for the researchers to adopt another perspective and acquire skills on the integration of Research Data Management into their processes, through the development of a Data Management Plan, which acts as a guarantee for the production and sharing of FAIR data. The researchers of the FrailSurvey project showed interest in implementing the recommendations, contributing to the practices and measures defined in the Data Management Plan and also acquired new skills for some stages of data management.